Proceedings of the 40th ACM Technical Symposium on Computer Science Education 2009
DOI: 10.1145/1508865.1508923
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors that influence computer science introductory course students to persist in the major

Abstract: This paper describes an exploratory study to identify which environmental and student factors best predict intention to persist in the computer science major. The findings can be used to make decisions about initiatives for increasing retention. Eight indices of student characteristics and perceptions were developed using the research-based Student Experience of the Major Survey: student-student interaction; student-faculty interaction; collaborative learning opportunities; pace/workload/prior experience with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 16 publications
0
60
0
10
Order By: Relevance
“…This kind of difficult subjects may decrease students' motivation and may cause dropout. It has been found that if the workload in the introductory class is too heavy compared with the students' level of experience, students more likely will not continue the computer science major [22]. In Estonia, some ICT students have learned programming before they start studying ICT at the higher education level, but some have their first contact with programming at university.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of difficult subjects may decrease students' motivation and may cause dropout. It has been found that if the workload in the introductory class is too heavy compared with the students' level of experience, students more likely will not continue the computer science major [22]. In Estonia, some ICT students have learned programming before they start studying ICT at the higher education level, but some have their first contact with programming at university.…”
Section: Introductionmentioning
confidence: 99%
“…Sissejuhatavate programmeerimiskursuste kohta on süste-maatilise kirjandusanalüüsi põhjal leitud, et need läbib vaid 67,7% üliõpi-lastest (Watson & Li, 2014). Kui sissejuhatavad õppeained on üliõpilaste jaoks liiga keerulised, siis on tõenäoline, et nad ei taha õpinguid sellel erialal jätkata (Baker, McDowell, & Kalahar, 2009).…”
Section: Ikt Erialade Spetsiifikaunclassified
“…Ka kirjandusest leiab väiteid, et just programmeerimine (Watson & Li, 2014) ja matemaatika (Divjak et al, 2010) on IKT-üliõpilaste jaoks keerulised. Sissejuhatavate õppeainete keerukus võib vähendada üliõpilaste soovi õpinguid jätkata (Baker et al, 2009) ning on ka IKT erialade puhul üks väljalange-mise põhjuseid. Lisaks leidsid nii väljalangenud kui ka õpinguid jätkanud üliõpilased, et õpingud ei vastanud nende esialgsetele ootustele, kuid erinevus seisnes selles, et õpinguid jätkanud üliõpilased suutsid õpingutega kohaneda ja nende edasised ootused õpingute suhtes muutusid.…”
Section: Erinevused õPpivate Ja Väljalangenud üLiõpilaste Vahelunclassified
“…It is a known fact that well prepared related teaching materials are directly associated with retention [17]. In the final survey, students responded about their interest in the assignments and laboratory works and also provided feedback about those.…”
Section: B Assignments and Labsmentioning
confidence: 99%